One vast winter count : the Native American west before Lewis and Clark - Calloway, Colin G. (Colin Gordon), 1953- (History of the American West., 2003)
"One Vast Winter Count offers a new look at the early history of the region - a blending of ethnohistory, colonial history, and frontier history. It features Native voices and perspectives; a masterful, fluid integration of a wide range of oral and archival sources from across the West; a dynamic reconstruction of cultural histories; and balanced consideration of controversial subjects and issues. Calloway offers an unparalleled glimpse at the lives of generations of Native peoples in a western land soon to be overrun."--Jacket